Diffusion Tensor Imaging of Mild to Moderate Blast-Related Traumatic Brain Injury and Its Sequelae - Levin, Harvey S.; Wilde, Elisabeth; Troyanskaya, Maya; Petersen, Nancy J.; Scheibel, Randall; Newsome, Mary; Radaideh, Majdi; Wu, Trevor; Yallampalli, Ragini; Chu, Zili; Li, Xiaoqi (Journal of neurotrauma, 2010)
To evaluate the effects of mild to moderate blast-related traumatic brain injury (TBI) on the microstructure of brain white matter (WM) and neurobehavioral outcomes, we studied 37 veterans and service members (mean age 31.5 years, SD = 7.2; post-injury interval 871.5 days; SD = 343.1), whose report of acute neurological status was consistent with sustaining mild to moderate TBI due to blast while serving in Iraq or Afghanistan. Fifteen veterans without a history of TBI or exposure to blast (mean age 31.4 years, SD = 5.4) served as a comparison group, including seven subjects with extracranial injury (post-injury interval 919.5 days, SD = 455.1), and eight who were uninjured. Magnetic resonance imaging disclosed focal lesions in five TBI participants. Post-concussion symptoms (Neurobehavioral Symptom Inventory), post-traumatic stress disorder (PTSD) symptoms (PTSD Checklist-Civilian), and global distress and depression (Brief Symptom Inventory) were worse in the TBI participants than the comparison group, but no group differences were found in perceived physical or mental functioning (SF-12). Verbal memory (Selective Reminding) was less efficient in the TBI group, but there were no group differences in nonverbal memory (Selective Reminding) or decision making (Iowa Gambling Task). Verbal memory in the TBI group was unrelated to PTSD severity. Diffusion tensor imaging (DTI) using tractography, standard single-slice region-of-interest measurement, and voxel-based analysis disclosed no group differences in fractional anisotropy (FA) and apparent diffusion coefficient (ADC). However, FA of the left and right posterior internal capsule and left corticospinal tract was positively correlated with total words consistently recalled, whereas ADC for the left and right uncinate fasciculi and left posterior internal capsule was negatively correlated with this measure of verbal memory. Correlations of DTI variables with symptom measures were non-significant and inconsistent. Our data do not show WM injury in mild to moderate blast-related TBI in veterans despite their residual symptoms and difficulty in verbal memory. Limitations of the study and implications for future research are also discussed.